PENGELOLAAN BIOMASA GULMA CROMOLAENA ODORATA DAN LIMBAH JAGUNG UNTUK MENINGKATKAN PRODUKTIVITAS BEBERAPA KULTIVAR BRASSICA OLERACEA VAR. BOTRYTIS. L DI TANAH ULTISOL - Suryantini Suryantini; Setiawan Setiawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
This study aims to determine which cultivars of Brassica oleracea var.Botrytis.L highest potential and determine the optimum dose combinations that produce productivity Brassica oleracea var. Botrytis.L best. The study was conducted at the Green-House Fak.Pertanian UPB from May to October 2014. Using RAL design. With Factorial consist of: Factor I (cultivars) with the code K: K1 = White Shot , K2 = Profta and K3 = Snow White. Factor II combination Cromolaena odorata (O), corn waste compost (J) and NPK fertilizer with C code consists of: C0 = Control; C1 = 100%NPK; C2 = 5%O+5% J+0%NPK; C3 = 5%O+2,5%J+50%NPK; C4 = 2,5%O+5% J+50%NPK; C5 = 5% O+5%J+50%NPK. Each treatment combination was repeated 3 times with 2 sample so that there are 108 plant experiments. Observation research through parameter; plant height (cm), number of leaves (leaf), weight of flower (gr), and dry weight (gr). Based on the analysis of waste compost corn and Chromolaena odorata, nutrient content is relatively high compared to NPK-manure. From the analysis of the interaction parameter is generated on a dry-weight that significantly, plant height, leaf number, the weight of flowert significantly affect compost while cultivars real effect on the number of leaves. The highest rates of plant height k1c3 (22.67cm), number of leaves k2c2 (22:00 leaf), dry weight k2c3 (45.75 gr) and weight of flower k3c3 (119.03 gr). Based on the data analysis of the influence of the observer and cultivars with waste compost corn and Cromolaena odorata more responded by vegetatitif growth while the generative growth is not maximized. Allegedly during the implementation of relatively high temperatures (>30oC)